MACROECONOMIC INFLUENCE ON INDONESIA'S SHARIA STOCK INDEX WITH GOLD PRICE AS INTERVENING VARIABLE - Novitasari, Salsa Billa; Meylianingrum, Kurniawati; Asnawi, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The objective of this study is to determine the macroeconomic influence on the Indonesian Sharia Stock Index with gold prices as an intervening variable. This study used a descriptive approach with quantitative methods. Data collection in this study used purposive sampling techniques. The data analysis used is path analysis using SPSS 26 software. The results of the study showed that macroeconomic variables inflation, exchange rates, and money supply had a significant effect on ISSI, while macroeconomic variables BI-Rate did not have a significant effect on ISSI. For macroeconomic variables, inflation and money supply have a significant effect on gold prices, while macroeconomic variables, exchange rates and BI-Rate do not have a significant effect on gold prices. The price of gold has a significant effect on ISSI. From the results of the study that gold prices can mediate inflation and BI-Rate against ISSI indirectly. And indirectly the price of gold cannot mediate the exchange rate and money supply against ISSI.